2022
DOI: 10.1016/j.esxm.2022.100508
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tadalafil in Penile Rehabilitation Started Before Nerve-Sparing Robot-Assisted Radical Prostatectomy: A Double-Blind Pilot Study

Abstract: Background Despite the widespread practice of nerve-sparing robot-assisted radical prostatectomy (nsRARP) for the treatment of localized prostate cancer (PCa), erectile dysfunction remains a significant sequela of radical prostatectomy. Aim This study aimed to compare the efficacy of tadalafil 5 mg once daily for erectile function recovery in patients who underwent nsRARP according to the timing of rehabilitation initiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…At 12 months, the recovery of unassisted EF was achieved in 80% and 71% of patients, respectively, with no statistically significant difference observed. Moreover, the authors concluded that preoperative tadalafil 5 mg/day may offer benefits in penile rehabilitation [ 70 ]. A systematic review informed researchers that treatments started before surgery (PFMT, oral medications, and vacuum devices) may aid in EF recovery and that frequent information delivery between the patient and partner also impact on sexual recovery [ 11 , 70 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…At 12 months, the recovery of unassisted EF was achieved in 80% and 71% of patients, respectively, with no statistically significant difference observed. Moreover, the authors concluded that preoperative tadalafil 5 mg/day may offer benefits in penile rehabilitation [ 70 ]. A systematic review informed researchers that treatments started before surgery (PFMT, oral medications, and vacuum devices) may aid in EF recovery and that frequent information delivery between the patient and partner also impact on sexual recovery [ 11 , 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors concluded that preoperative tadalafil 5 mg/day may offer benefits in penile rehabilitation [ 70 ]. A systematic review informed researchers that treatments started before surgery (PFMT, oral medications, and vacuum devices) may aid in EF recovery and that frequent information delivery between the patient and partner also impact on sexual recovery [ 11 , 70 ]. However the recommended time to start penile rehabilitation is 1–4 weeks after RP [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations